On the reprieve: deconstructive ethics and Primo Levi's 'Moments of Reprieve'. Issue 11 (2nd November 2022) - McAvan, Emily
ABSTRACT: In this article, I discuss Primo Levi's Holocaust survivor testimonies in Moments of Reprieve, arguing that these stories illuminate a concept I term 'the reprieve'. Using the reprieve as an undecidable word I argue that the reprieve is a moment of humanisation in the camps in which our inherent responsibility for one another becomes clear. Though it does not offer freedom or salvation, it does allow for a moment of loosening in the midst of repression and horror.